COMPARATIVE STUDY OF THE CONCEPT OF REBORN ACCORDING TO I PETER 1:13-25 WITH THE HINDU RELIGION - Valentino Wariki; Hiruniko Ruben Siregar; Tomsa Josestian Manullang; Joshia Joandika B. M. Christi (Diegesis : Jurnal Teologi, 2023)
Rebirth is generally understood as the process in which a person's soul moves into a new body after death. Rebirth is a concept understood by Christianity and Hinduism but from different perspectives. This study uses a qualitative method in which the researcher will explore the meaning of 1 Peter 1:13-25 through exegesis and conduct a comprehensive study on Rebirth. The purpose of this paper is to provide a complete explanation of the concept of Rebirth in Christianity based on the text of 1 Peter 1:13-25 and in Hinduism based on the Veda. This paper's results find differences in the understanding of Rebirth between Christianity and Hinduism, but interesting similarities are also found. From these findings, the researcher invites every reader to understand and appreciate every difference that exists to foster a sense of unity among Christians and Hindu.